Perancangan Ulang Vacuum Evaporator Untuk Pengering Madu Kapasitas 50 Liter - Afrian Afrian; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Honey is unique product from insect which contain high percentage of carbohydrates. Honey obtained from the forest contains high water content due to climate change. The reduction of water content honey need a machine such as evaporator. Evaporator is a separator machine water content honey using pressure and temperature. Evaporator parts of such as: vessel, vacuum pumps, electric motors, electric heater, and control system. This research used vessel as a place honey processing. Vessel is pressure of fluid storage container, part of vessel such as: shell, head, opening and support. This research explains how to design the pressure vessel using standard of ASME section VIII Boiler and Pressure Vessel, obtain dimension from mixer such as a screw and impeller. Results from this research obtained shell inner diameter is 22.55 inch with a thickness of 0.142 inch, the outer shell diameter is 24.81 inches with a thickness of 0142 inch, head diameter is 22.55 inch with a thickness 0.142 inch, opening (diameter nozzle on the vacuum pump 1 inch with a thickness of 0.065 inch and diameter nozzle on water level control 1 inch with a thickness of 0.065 inch). Obtained dimension screw with a diameter 4 inch and pitch distance of screw 3.2 inch with screw angle 22o. obtain dimensions impeller Da = 11.28 inch, w = 2.26 inch, Dd = 4.51 inch dan L = 2.82 inch.Keywords : Evaporator, Pressure Vessel, System Control